Representation of Cosmological Concepts at the Taman Mayura Site, Cakranegara District, Mataram City: A Spatial Archaeology Study - Nicolas Nesta Rama Umbu Lado (Universitas Airlangga, 2026)
Spatial organization in royal gardens often reflects cosmological concepts rooted in Hindu-Buddhist cultural traditions. Taman Mayura is a royal garden site in Mataram City characterized by a complex spatial arrangement consisting of pavilions, ponds, and temples. This study aims to examine the representation of cosmological concepts within the site’s spatial organization using a spatial archaeological approach. The research applies a qualitative descriptive method through the analysis of the distribution, relationships, and orientation of architectural elements. The results show that the site is organized into three spatial zones: (1)jaba luar; (2) jaba tengah; and (3) jeroan that forms a hierarchical spatial structure. This pattern reflects the concept of Tri Maṇḍala, while the presence of Bale Kambang at the center of a pond on Gili Kencana symbolizes Mahāmeru surrounded by the cosmic ocean. Therefore, the spatial arrangement of Taman Mayura reflects both the organization of a royal garden landscape and cosmological ideas in the past.